DETECTION OF INSULIN SECRETION AND LIPID PROFILE FOR CHROMIUM-SUPPLEMENTS AGAINST H5 INFLUENZA VACCINATION IN LAYERS - Mohammed Fadhil Taleb,; A. H. Ulaiwi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to determine whether chromium (Cr III) supplements have a beneficial effect on the insulin secretion and lipid profile of layers vaccinated against H5 avian influenza (AI). The study included serological parameter by ELISA kit and biochemical parameter for lipid profile test as well as to compare between highly pathogenic avian influenza (HPAI) recombinant (rH5N1) vaccine and classical (cH5N8) vaccine. The study was designed as follow: {G1: given rH5N1 vaccine only; G2: given cH5N8 only; G3: given rH5N1 with Cr III supplement; G4: given cH5N8 with Cr III supplement; G5: given Cr III supplement; G6: is negative control with no vaccination or supplementation}. Levels of insuline at 21 days old there were showed a significant increase in G3 and G5 as compared with another groups. At 42 days old, G3, G4 and G5 revealed the highest levels as compared with another groups. Similarity results for 60 days old groups. The results of lipid profile test at 60 days old showed the lowest level of cholesterol in G5 as compared to another groups and lowest levels of vLDL in G3, G4 and G5. However, there were no significant differences in triglycerides (Tri.Gs), HDL and LDL levels in all groups. In conclusion, Cr III supplementation can improve insulin secretion in layers vaccinated with AI H5 vaccines and it has a positive impact on lipid profile.